Z?hir? School and Metaphor:The Case of Ibn Hazm - Arpa, Abdulmuttalip (Sakarya University, 2012)
In the history of Islamic thought, a number of various approaches have emerged to try and interpret and understand the Qur'?n. One of these approaches is a Z?hir? thought system which considers the literal meaning of the word of Allah (God) as basic reference to the first degree and seeks the contextual meaning of the Qur’an in its linguistic foundation. The Z?hir? school emerged for the first time in the early third century AH from a reactionary line against the systems of thought during the time, forming a systematic structure with Ibn Hazm. Ibn Hazm entered into a commentary method which was unique to him, to try and provide an objective meaning of religion. In this article, in order to provide a foundation, we have provided information about the contents of the Qur'?n, its style and the significance of the metaphorical language in sacred texts in order to establish a framework for our topic. Then we have studied the definition of Z?hir? thought and the understanding of ta’w?l and dealt with the opinions of Ibn Hazm on metaphor/maj?z which shaped his thought system. The main purpose of this article is to determine the original interpretation method and its scope in Islamic thought tradition on which the Z?hir? thought system developed.

İslam düşünce tarihinde Kur'an'ı anlama ve yorumlama konusunda birçok akım ortaya çıkmıştır.Bu yaklaşım tarzlarından birisi de lafzın dildeki zahirî anlamını birinci derecede referans kabul eden ve Kur'an'ın anlam örgüsünü dilsel zeminde arayan zahirî düşünce sistemidir. İlk defa hicrî üçüncü asrın başlarında daha çok dönemin düşünce yapısına tepkisel bir çizgide ortaya çıkan Zahirîlik, İbn Hazm ile birlikte sistemli bir yapıya kavuşmuştur. İbn Hazm dinin nesnel anlamınaulaşmak için kendine has bir yorum metodu arayışına girer. İşte bu çalışmada konuya bir zemin oluşturması amacıyla öncelikle genel anlamda Kur'an'ın muhtevası, üslûbu ve mecazî dilin kutsal metinlerdeki önemi hakkında bilgi verildi; ardından zahirî düşünce'nin tanımı ve te'vîl anlayışı incelendikten sonra İbn Hazm'in te'vîl anlayışını şekillendiren mecazla ilgili görüşleri üzerinde duruldu. Zahirî düşünce'nin geliştirdiği özgün yorum metodunun ortaya konulması ve İslam düşünce geleneğindeki yerinin tespiti çalışmanın temel amacını teşkil edecektir.
ZÂHİRÎLİK VE MECÂZ:İBN HAZM ÖRNEĞİ